US hospital webpages on atrial fibrillation ablation: A potential source for misinformation. (23rd July 2022) - Rajyaguru, Chirag; Sandhu, Uday; Hadjis, Alexios; Dere, Juliana; Panchal, Somya; Ja, Austin; Ong, Nicholas; Yu, Stephen; Yu, Jeremy; Lee, Sun Yong; Lee, Byron K.
Abstract: Introduction: Atrial fibrillation (AF) ablation is performed worldwide. To attract patients, hospitals frequently have webpages that tout the success of the procedure. The information disseminated to the public via these webpages has not been systematically reviewed. Our objective was to assess accuracy of information delivered to the public on hospital websites in regard to atrial AF ablation. Methods: From July 2019 to January 2020, we performed a Google search for all US hospitals registered with Medicare to see if they had a webpage describing AF ablation. Resulting hospital webpages were abstracted for data on AF ablation success rates and risks. Success rates over 86%, the highest success rate in the medical literature, were deemed exaggerated. Results: Among 4805 hospitals, 487 had webpages describing AF ablation and 33 discussed success rates of AF ablation. Twelve percentage reported exaggerated success rates, 3% referred to ablation as a cure, and 2.8% referred to ablation as a tool to eliminate AF. Less than 10% of webpages describing AF ablation noted the potential need for a second ablation to achieve the stated success rate and merely 16% mentioned risks of the procedure. One percentage of webpages directly suggested AF ablation could reduce risk of stroke while others indirectly suggested it by discussing cessation of anticoagulation. Two webpages mentioned reduced mortality. Conclusion: US hospital webpages rarely discuss AF ablation. When discussed, there were concerning unsubstantiated claims regarding mortality, stroke prevention, and need for medical therapy. This could lead to some patients undergoing AF ablation based on faulty understanding.